Didactic Support for the Development of Methodological Competence of Future Primary School Teachers - Nurillayev Samad Safarovich; Khakimova Ma’mura Mukhammadiyevna (Scientific Trends, 2025)
This article discusses didactics, the purpose, tasks, and principles of didactic support in developing the methodological competence of future primary school teachers.
Keywords: Didactics, competence, principles, Great Didactics, fundamental, management, didactic support.